THE EFFECT OF PROBLEM BASED LEARNING (PBL) BASED E-MODULE ASSISTED BY SMART APPS CREATOR APPLICATION ON STUDENT LEARNING MOTIVATION (STUDY ON RESEARCH OF GRADE XI STUDENTS OF SMA NEGERI 1 KECAMATAN GUGUAK DISTRICT): Pengaruh E-Modul Berbasis Problem Based Learning (PBL) Berbantuan Aplikasi Smart Apps Creator Terhadap Motivasi Belajar Siswa (Studi Pada Penelitian Siswa Kelas XI SMA Negeri 1 Kecamatan Guguak) - Mutiara; Annur Fitri Hayati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to determine the effect of e-modules based on problem based learning (PBL) assisted by the Smart Apps Creator (SAC) application on student learning motivation. This type of research is a quasi-experiment with a population of class IX students at SMA N 1 Guguak District. Sampling used purposive sampling technique. The total sample was 66 class XI students at SMAN 1 Guguak District who were divided into 2 groups, namely 32 for the control class group and 34 for the experimental class group. Based on the results of the data using the normality test and homogeneity test, the results obtained were that the data had a normal distribution and homogeneous variance. Then proceed with hypothesis testing using the independent sample t-test posttest data from the student learning motivation questionnaire (experiment and control). The result obtained was 0.004 < 0.005 so Ho was rejected. So it is concluded that there is a significant influence of the use of PBL based e-modules assisted by SAC applications on student learning motivation